Karakteristik Moda Angkutan Umum Berbasis Online Di Jakarta Selatan - Mustaqima, Zahra Zakiyya; Agustin, Imma Widyawati; Utomo, Dadang Meru (Jurnal Tata Kota dan Daerah, 2018)
South Jakarta as the center of residential and economic activities in Jakarta, experienced population growth every year. The increasing population of Jakarta Selatan resulted in an increase in various needs, such as the need for mobilization. The need for mobilization is supported by the transportation in South Jakarta in the form of private vehicles and public transportations. Along with the technology development, the information technology began to be applied in public transport as a solution to the problem of congestion and the problem of conventional public transport. The main purpose of this research is to determine the characteristics and differences of online-based public transportation is South Jakarta. This research use descriptive analysis. Based on the results of descriptive analysis, the differences of online-based transportaion depend on the service provider company. Differences from every online-based public transportation companies are origin country and service coverage, type of vehicle used, service facilities, payment method, point and reward features, peak hours, motorcycles and cars fare, as well as additional fees of cancellation.Keywords: Online based public transportation, South Jakarta